Can pulse oxymetry be used as a routine screening tool in early diagnosis of critical congenital heart diseases in newborns? - Reddy, Gomathi Chenna; Devaraj, K. N. (International Journal of Contemporary Pediatrics, 2018)
Background: Unrecognition or delayed diagnosis of severe congenital cardiac diseases (CCD) can lead to cardiac failure, cardiovascular collapse and death. Pulse oximetry can be used as a screening tool for detection of critical CCD (CCCD) in newborns. We conducted this study to correlate pulse oximetry findings in asymptomatic newborns to detect CCCD and coarctation of aorta. Methods: All babies delivered in our hospital were included; after clinical evaluation, pulse oximetry screening was done 12 hours after delivery, taken in three extremities (Right thumb, left thumb and left great toe). If the readings were <95% in any of the limbs, they were further evaluated to detect cardiac defects. Results: Of 800 babies, 54.4% were males and 66.1% were delivered by normal vaginal delivery. Antenatal scan of all were normal. Mean±SD birth weight was 2.92 kg ±.29 ranging 2.14 Kgs-3.80 kgs. Oxygen saturation was >95% in 799 babies, there was no significant clinical findings, and were negative for pulse oxymetry screening; one baby had positive pulse oximetry screening (<95%) with ‘ejection systolic murmur’ over left 2nd and 3rd intercostal space. There was no evidence of cyanosis, oedema or tachypnoea. Pulse oximetry reading was 88% in right thumb, 90% in left thumb and 92% in left great great toe. Echocardiography showed Atrial Septal Defect, Ventricular Septal Defect with Pulmonary Stenosis. Conclusions: Pulse oximetry is a non-invasive, reliable, and useful screening tool for an early detection of CCCD in newborns. The combination of pulse oximetry and clinical judgement is needed.